2019
DOI: 10.1136/jech-2019-212557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection, cervical intraepithelial neoplasia and cervical cancer in imprisoned women worldwide: a systematic review and meta-analysis

Abstract: Background and objectivesImprisoned women have higher rates of abnormalities at cervical screening and some studies suggest that cervical cancer is the most common cancer in this population. The aim of this work was to summarise the current evidence on the prevalence of human papilloma virus (HPV) infection, cervical cancer and precancerous lesions in women in prison worldwide and to compare these rates with the general population.MethodsWe systematically searched and reviewed published and unpublished data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Diffuse and marked p16 expression usually indicates the presence of HPV infection in squamous cell carcinoma of the uterine cervix, pharynx, and esophagus [15,16,28]. Cao et al reported that the presence of HPV was significantly correlated with p16 immunoreactivity in esophageal squamous cell carcinoma and suggested the p16 immunoreactivity as a good marker for HPV infection [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse and marked p16 expression usually indicates the presence of HPV infection in squamous cell carcinoma of the uterine cervix, pharynx, and esophagus [15,16,28]. Cao et al reported that the presence of HPV was significantly correlated with p16 immunoreactivity in esophageal squamous cell carcinoma and suggested the p16 immunoreactivity as a good marker for HPV infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, p16 protein overexpression is also considered a surrogate marker of oncogenic human papillomavirus (HPV) infection. HPV infection plays a pivotal role in carcinogenesis of oropharyngeal, uterine cervical, and perianal cancers [9,15,16]. Following the entry of virion via endocytosis, the virus establishes a persistent infection as a viral episome or integrates into the host genome [17].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Cervical cancer (CC) is a familiar malignant tumor, which causes death and suffering to women around the world 1,2 . Besides human papillomavirus (HPV) infection, tobacco smoking, low socioeconomic status, immunosuppression, early age at first intercourse, and plenty of sexual partners are linked to higher risk of CC 3,4 . At present, surgery, radiation therapy, hormonal therapy, targeted therapy, and chemotherapy are the major strategies for cancer treatment, including CC 5 .…”
Section: Introductionmentioning
confidence: 99%
“…tobacco smoking, low socioeconomic status, immunosuppression, early age at first intercourse, and plenty of sexual partners are linked to higher risk of CC. 3,4 At present, surgery, radiation therapy, hormonal therapy, targeted therapy, and chemotherapy are the major strategies for cancer treatment, including CC. 5 The majority of early cancer is detected via refined detection technology, and the mortality of CC has apparently declined, and the prognosis rate has been elevated.…”
mentioning
confidence: 99%
“…In this respect, the human papillomavirus (HPV), the most important cause of cervical carcinoma, has been studied widely in numerous populations. Many of the risk factors for HPV infection (especially the high-risk type), such as cigarette use, immunosuppression, and low socioeconomic pro les are known to cluster in vulnerable populations, such as people incarcerated in prisons [6], and women in prison systems are likelier to have traded sexual favors for money or drugs [7]. This increases the risk of cervical intraepithelial neoplasia and cervical carcinoma among these women.…”
Section: Introductionmentioning
confidence: 99%